臺灣地區大專院校教師對學校評價的影響機制：學校屬性與教師分級的區隔作用 Taiwanese College Instructors' Evaluation of Their Schools: The Differences Among School Attributes and Instructor Ranks - 林俊瑩 Chunn-Ying Lin; 謝亞恆 Ya-Heng Hsieh; 陳成宏 Cheng-Hung Chen (National Taiwan Normal University, 2014)
在高等教育經營環境日趨嚴苛的情形下，如何讓所屬教職員能認同於學校，並給予高評價，願意努力付出，增進學校榮譽，提高競爭力，當是高等教育經營管理重要的課題。然而，在如何促進大專院校教師對任教學校有高度正面評價的重要問題上，卻仍少有研究關注於不同職場屬性（如公／私立、綜合／科技），與教師分級制度所可能導致的差異性，並深入探討造成差異性的因素。基於此，本研究以臺灣高等教育整合資料庫的大專教師調查資料，對上述重要的研究議題進行分析。研究結果顯示：相較於私立技職院校，公立大學教師在教師聘用、專業發展、待遇福利，職場氛圍等工作環境之滿意度較低，而使其對所任教的學校評價較低。其次，公立技職教師，對於教師任用、專業發展、待遇福利等方面的滿意度都低於私立技職院校，因而對所任教學校的評價也就明顯較低。另外，教授與副教授對學校設備、人力資源、教師任用、專業發展、待遇福利與職場氛圍等，明顯比助理教授有較高的滿意度，因而對所任教的學校也就有較高的評價，而助理教授覺得學校較不夠友善，給的評價也就最低。 Managing higher education is becoming increasingly difficult. How to strengthen the identifications, evaluations, and dedications of faculties to the reputation and competitiveness of their institutions is a critical issue in managing higher education. Little research on how to promote the identification of college instructors with their institutions has focused on differences among job attributes (e.g., public/private, general/technological, and science) and instructor ranks as well as the factors contributing to the differences. This study attempted to answer these questions by using a sample of college instructors obtained from the Taiwan Integrated Postsecondary Education Database. The results showed that compared with instructors at private vocational colleges, instructors at public universities were less satisfied with employment, professional development, salary and benefits, and workplace atmosphere of their institutions and tended to assign relatively lower ratings to their schools. In addition, instructors at public vocational colleges were less satisfied with employment, professional development, and the salary and benefits of their institutions compared with their counterparts at private vocational colleges, which lead to the low rating of their institutions. Analysis of differences according to rank revealed that professors and associate professors were significantly more satisfied than assistant professors with their schools in the aspects of facilities, human resources, employment, professional development, salary and benefits, and workplace atmosphere. Thus, they assigned higher ratings to their schools. Associate professors tended to identify their schools as insufficiently friendly, and thus, their ratings of their schools were the lowest.